2000
DOI: 10.1007/bf02817564
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofCryptococcus neoformans in clinical specimens

Abstract: Cryptococcus neoformans isolated from various clinical materials in 14 cases, was identified by (1) cultivation on Sabouraud glucose agar and CHROMagar Candida, (2) microscopic examination of Indian-ink-stained preparations and (3) determination of biochemical properties (assimilation and fermentation of saccharides, assimilation of KNO3, production of urease and phenol monooxygenase). C. neoformans was determined in five specimens from paediatric patients in the intensive care unit and in nine specimens from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Of these, 143 studies were included in the data analysis (Tables, references, Supplemental Digital Contents 1, http://links.lww.com/INF/F353; 2, http://links.lww.com/INF/F354) and 25 did not meet the inclusion criteria. 8,13,15,17–38 A total of 1048 children were included in the data analysis. The 103 case reports of pediatric cryptococcal disease are summarized in Table, Supplemental Digital Content 1, http://links.lww.com/INF/F353.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 143 studies were included in the data analysis (Tables, references, Supplemental Digital Contents 1, http://links.lww.com/INF/F353; 2, http://links.lww.com/INF/F354) and 25 did not meet the inclusion criteria. 8,13,15,17–38 A total of 1048 children were included in the data analysis. The 103 case reports of pediatric cryptococcal disease are summarized in Table, Supplemental Digital Content 1, http://links.lww.com/INF/F353.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial isolates were further studied for their morphological and biochemical characteristics. Dorko et al, (2000) reported that Cryptococcus neoformans are white, grey in colour, smooth in texture and had raised colony.…”
Section: Characterization Of Bacterial Isolatesmentioning
confidence: 99%